Weight change during chemotherapy as a potential prognostic factor for stage III epithelial ovarian carcinoma: A Gynecologic Oncology Group study - Hess, L.M.; Barakat, R.; Tian, C.; Ozols, R.F.; Alberts, D.S. (Gynecologic oncology, 2007)
Platinum/Paclitaxel-based chemotherapy is a current treatment for advanced epithelial ovarian cancer. We sought to explore the association between weight change during treatment and survival, as well as the association between pre-chemotherapy body mass index (BMI) and survival. A retrospective data review was conducted of 792 advanced ovarian cancer patients who participated in a phase III randomized trial of cisplatin/paclitaxel versus carboplatin/paclitaxel. Pre-chemotherapy BMI was calculated following surgery. Weight change was defined as the ratio of body weight at completion of protocol therapy to pre-chemotherapy body weight. Progression-free survival (PFS) and overall survival (OS), classified by BMI or relative weight change, were estimated by Kaplan–Meier, and associations were assessed using a Cox model controlled for known prognostic variables (age, race, performance status, histology, tumor grade, tumor residual and treatment group). There was no association between pre-chemotherapy BMI and survival. There was a significant relationship between median OS and weight change as follows: > 5% decrease = 48.0 months; 0–5% decrease = 49.3 months; 0–5% increase = 61.1 months; and > 5% increase = 68.2 months. Adjusted for covariates, the relative risk of death increased by 7% for each 5% decrease in body weight (HR = 0.93, 95% CI = 0.88–0.99; p = 0.013). Change of body weight during primary chemotherapy was a strong prognostic factor for overall survival. Loss of body weight during primary therapy is an indicator for poor OS; weight gain is an indicator for improved survival. This study supports the development of strategies to minimize weight loss that can be assessed in a prospective, randomized study to improve patient outcomes.